Exigências nutricionais de proteína e energia de cordeiros Texel - Griebler, Letieri (2015)
The objective of this study was to determine the energy and protein requirements for maintenance and weight gain in growing Texel lambs. Forty-two non-castrated male lambs, weaned at 80 days of age were housed in individual stalls. After adaptation to experimental conditions, six lambs were slaughtered to compose the reference animals and twenty-four animals were fed ad libitum and slaughtered at 25, 30, 35 or 40 kg body weight (BW). Twelve animals were submitted to two levels of food restriction (70 or 55% of ad libitum intake; six per group). It was determined corporal content of nitrogen and energy. The food-restricted lambs were slaughtered together with those fed ad libitum (40 kg BW). Another six lambs were assigned to a digestibility trial, with the objective of evaluate the nutritional value of the diet in the different consumption levels. The animals were individually housed in metabolic cages according a double 3x3 Latin square design. Daily samples of remains, feces and urine were collected during experimental period, grouped by animal and stored for subsequent laboratory analysis. The protein concentration in wool free body did not differ with the increase of empty body weight, even when considering the wool-retained protein. The body energy concentration increased with the increase of empty body weight. The net energy requirement for maintenance was 43.39 kcal/kg PV0,75/day and metabolizable energy was 63.43 kcal/kg PV0,75/day. The efficiency of metabolizable energy utilization for maintenance (km) was 0.72. Nitrogen endogenous excretion was 179.6 mg/kg PV0,75/day, corresponding to a protein requirement for maintenance of 1.12 g/kg PV0,75/day. The metabolizable and liquid protein requirement for maintenance were the same (1.12 g/kg PV0,75/day) once efficiency of metabolizable protein for maintenance (kpm) was equal to 1.0. The liquid energy and protein requirement for an average daily gain of 250 g in lambs with 20 or 40 kg body weight were 551 and 790 kcal/day and 36.7 and 35.5 g/day, respectively. The efficiency use of metabolizable energy for gain (kg) was 0.55, whereas the efficiency of metabolizable protein for gain (kpg) was 0.59. The energy and protein requirements for maintenance of Texel lambs between 20 and 40 kg live weight were lower than those reported by international systems (ARC, 1980; NRC 1985, 2007; AFRC 1993 and CSIRO 2007) . The energy requirements for weight gain are higher than reported by NRC (2007), but lower than other systems, as well as the protein requirements for gain are lower than those recommended by the International Systems of sheep.